The Implementation Perda Nomor 7 Tahun 2015 tentang Pengelolaan Sampah in Bone Regency - Ibnu Hasyim; Achmad Dahlan Abdullah; M. Awaluddin; Feby Triadi (Jurnal Ad'ministrare, 2020)
Solid waste management is aimed at overcoming and preventing environmental pollution caused by both domestic and non-domestic waste. This study used a purely qualitative approach with a cross-section research time dimension. This research is a qualitative descriptive study. The data collection techniques used were in-depth interviews and documentation techniques. The data analysis used was data reduction, data presentation, and conclusion drawing. The results showed that the people who care about waste management are carried out by a small proportion of residents. A small portion of the community wants to process their household waste by making compost and various handicrafts. Meanwhile, the transportation of waste to the TPA is also not optimal, because the amount of waste generated every day cannot be transported all. Also, the readiness of the transport fleets is not sufficient when compared to the amount of waste produced each day